161k views
4 votes
Y=3x-5 y=6x-8 show all steps and write the solution

User Henry C
by
5.1k points

2 Answers

6 votes

Step 1: Set the two equations equal to each other and solve for x.

3x -5 = 6x - 8

3x + (-5+5) = 6x -8 + 5

(3x - 6x) = (6x - 6x) - 3

-3x/-3 = -3/-3

x = 1

Step 2: To solve for y take one of the given equation of your choice (for the purpose of this explanation I will only do y = 3x - 5) and replace x with 1, then solve for y

y = 3(1) - 5

y = 3 - 5

y = -2

(1,-2)

Check:

-2 = 3(1) - 5 ---> - 2 = -2

-2 = 6(1) - 8 ---> -2 = -2

Hope this helped!

User Daniel Congrove
by
5.9k points
0 votes

Answer:

x=1

and y= -2

Explanation:

y=3x-5 y=6x-8

On equating the two equations:

3x-5= 6x-8

Taking terms of x on one side and constant terms on the other

6x-3x= 8-5

3x= 3

Dividing both sides by 3, we get

x=1

Now, putting value of x in y=3x-5, we get

y=3-5

= -2

Hence, Solution is:

x=1 and y= -2

User Greg Campbell
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.